2004
DOI: 10.1111/j.1365-2427.2004.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modelling and spatial mapping of freshwater fish and decapod assemblages using GIS and neural networks

Abstract: 1. We used stream fish and decapod spatial occurrence data extracted from a national database and recent surveys with geospatial landuse data, geomorphologic, climatic, and spatial data in a geographical information system (GIS) to model fish and decapod occurrence in the Wellington Region, New Zealand. 2. To predict the occurrence of each species at a site from a common set of predictor variables we used a multi-response, artificial neural network (ANN), to produce a single model that predicted the entire fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 74 publications
4
92
2
Order By: Relevance
“…Davey et al 2011). At landscape scales interactions between variables such as slope and distance inland may be likely RootV Water depth (log(depth*100)) LogD Presence of cover for large eels (0 to 10) COVER to influence migratory fish, such as eels (Joy & Death 2004). We therefore repeated all partial constrained ordinations after having included second order interactions between all predictor variables.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Davey et al 2011). At landscape scales interactions between variables such as slope and distance inland may be likely RootV Water depth (log(depth*100)) LogD Presence of cover for large eels (0 to 10) COVER to influence migratory fish, such as eels (Joy & Death 2004). We therefore repeated all partial constrained ordinations after having included second order interactions between all predictor variables.…”
Section: Methodsmentioning
confidence: 99%
“…Our work suggested that, to adequately represent patterns in densities, models will need to incorporate both local-scale and landscapescale variables that include interactions and nonlinear relationships. Further studies are in progress, but it seems likely that best approaches will require relatively long-term data and sophisticated modelling tools such as mixed-effects models (Beˆche et al 2009), regression trees (Elith et al 2008) or artificial neural networks (Joy & Death 2004). Consideration of diel variations in local-scale habitat preferences, as has been investigated for other New Zealand native fishes (Davey et al 2010), may also be an area which would benefit from further research.…”
Section: Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations